Neuromyelitis Optica Spectrum Disorder: A Case Report - Sėdžius, Paulius; Šataitė, Gintarė; Gleiznienė, Rymantė; Musneckienė, Dalia (Neurologijos seminarai, 2024)
Neuromyelitis Optica Spectrum Disorder (NMOSD) is a rare inflammatory and demyelinating disease of the central nervous system affecting the optic nerves and the spinal cord. Diagnosis of NMOSD is based on the Diagnostic Criteria of the International Panel for NMOSD diagnosis (IPND). This paper introduces the case of a man who developed bilateral blindness and acute paralysis of legs. The MRI scan of the brain and spinal cord revealed lesions characteristic of transverse myelitis and bilateral optic neuritis. The serum test performed was negative for aquaporin-4-IgG (AQP4-IgG). Based on the diagnostic criteria of IPND, the patient was diagnosed with NMOSD and prescribed with immunosuppressive methylprednisolone IV once a day for five days and changed to prednisolone PO. The clinical case described here demonstrates the importance of assessing the clinical symptoms as well as brain and spinal cord images in the diagnosis of NMOSD in seronegative AQP4-IgG patients.
Keywords: Neuromyelitis Optica Spectrum Disorder; aquaporin-4 antibodies